EFFECT OF DRYING TECHNIQUE ON PHYSICAL QUALITY AND ANTI-INFLAMMATORY ACTIVITY OF WILD BETEL LEAVES (Piper sarmentosum Roxb. ex Hunter) EXTRACT - Fahleni Fahleni; Yuslia Noviani; Syarifah Ramadhani (Fakultas Farmasi Universitas Pancasila, 2018)
Kaduk betel leaves (Piper sarmentosum Roxb. ex. Hunter) contain flavonoids and alkaloids that have anti-inflammatory activity. Processing thick extract into a dry extract is required to determine the appropriate dose and increase the homogeneity. The purpose of tahhis study was to determine the effect of drying method to physical properties of dried powder and its antiinflammatory activity. Thick extract was dried using maltodextrin and lactose as adsorbents with concentrations of extract-adsorbent ratio 1: 1, 1: 2 and 1: 3. Method of drying were freeze drying and adsorbent. The evaluation results based on organoleptic dried powder, water content and flow properties. The water content of dried powder which is dried by freeze drying is smaller than that of the adsorbent. Organoleptic and flow properties of freeze dried powder results were also better. The best dried powder in each method tested its anti-inflammatory activity using BSA. The test results showed that the anti-inflammatory activity of dried extract of freeze drying (extract-maltodextrin 1:3) have higher activity with IC50 551.79 ppm compared to dried extract with adsorbent (extract-maltodextrin 1:3) 598.30 ppm.